الممارسة الرياضية في الوسط المدرسي ودورها في تحسين بعض مها ا رت الاتصال التربوي لدى تلاميذ الطور الابتدائي - العلوي أحمد; الهاشمي حنة (My University, 2024)
تهدف الدراسة الحالية إلى التعرف على الممارسة الرياضية في الوسط المدرسي ودورها في تحسين بعض مهارات الاتصال التربوي لدى تلاميذ الطور الابتدائي ، حيث تم استخدام المنهج الوصفي، وتكونت عينة الدراسة من(40) معلما، حيث تم استخدام برنامج الحزم الإحصائية للعلوم الاجتماعية (SPSS) لمعالجة البيانات، وتوصلنا الى النتائج التالية : - توجد فروق ذات دلالة إحصائية في تحسين مهارات الاتصال اللفظي بين الأستاذ والتلاميذ في الوسط المدرسي لطور الابتدائي. - توجد فروق ذات دلالة إحصائية في تحسين مهارات الاتصال الغير لفظي بين الأستاذ والتلاميذ في الوسط المدرسي لطور الابتدائي . - توجد فروق ذات دلالة إحصائية في تحسين مهارات الاتصال اللفظي وغير اللفظي بين الأستاذ والتلاميذ في الوسط المدرسي لطور الابتدائي
The current study aims to identify mathematical practice in the school environment and its role in improving some educational communication skills among primary school students, where the descriptive approach was used, and the study sample consisted of (40) teachers, where the Statistical Package for the Social Sciences (SPSS) program was used to address data, and we reached the following results: - There are statistically significant differences in improving verbal communication skills between the teacher and the students in the primary school setting. - There are statistically significant differences in improving non-verbal communication skills between the teacher and the students in the primary school setting. - There are statistically significant differences in improving verbal and non-verbal communication skills between the teacher and the students in the primary school setting